2021
DOI: 10.26651/allelo.j/2021-53-1-1330
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green manure of wild rocket (Diplotaxis tenuifolia L.) on cucumber rhizosphere fungal community

Abstract: In pot culture, we evaluated the effects of green manure of wild rocket (Diplotaxis tenuifolia (L.) DC.) on cucumber (Cucumis sativus L.) rhizosphere fungal community composition. Cucumber rhizosphere fungal composition was analyzed by high-throughput amplicon sequencing of fungal ITS regions. Results showed that cucumber seedling rhizosphere fungal community composition was different between the fallow treatment and green manure treatment. However, green manure treatment did not affect the cucumber seedlings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…BOROZAN et al 2015) showed that mixed green manure of legumes and annual grasses can increase the diversity and quantity of actinomycetes and bacteria. ZHANG et al (2021a) showed that the application of green manure of wild rockets could increase the number and abundance of Ascomycota near cucumber roots.…”
Section: Effect Of Green Manure On Soil Microorganismsmentioning
confidence: 99%
“…BOROZAN et al 2015) showed that mixed green manure of legumes and annual grasses can increase the diversity and quantity of actinomycetes and bacteria. ZHANG et al (2021a) showed that the application of green manure of wild rockets could increase the number and abundance of Ascomycota near cucumber roots.…”
Section: Effect Of Green Manure On Soil Microorganismsmentioning
confidence: 99%
“…Soil and residue samples were incubated for 15 days at 28 • C, while the soil moisture was maintained at 60% water holding capacity by adding distilled water. After incubation, pepper seedlings were planted in pots and kept in a greenhouse (day and night temperature of 28 and 20 °C, relative humidity range of 60-80%, 16 h light/8 h dark cycle) [28]. The experiment involved 4 treatments, with 3 replicates for each treatment and 3 pots for each replicate.…”
Section: Greenhouse Experiments Designmentioning
confidence: 99%